Pre-service Teachers’ Experiences in Handling Reticent Students During Teaching Practicum: Challenges and Strategies - Jose Argo Tanore; Listyani - Listyani (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
This study looked at the experience of English as a Foreign Language (EFL) pre-service teachers handling reticent students during their teaching practicum. Reticent students are characterized by reluctance or hesitance to participate or engage in classroom discussions and activities actively. Teaching practicum is a hands-on educational experience that allows pre-service teachers to apply classroom theories and teaching strategies in real-world settings, fostering their professional growth under the guidance of experienced educators. Previous studies have explored teacher perceptions and strategies for addressing student reticence, but less attention has been given to pre-service teachers' experiences. The study employs a qualitative research design, conducting semi-structured interviews with five pre-service teachers who have completed their teaching practicum. The interviews explore the participants' experience focusing on the challenges and strategies in handling reticent students. The findings revealed common challenges faced by the participants and the strategies employed to handle reticent students. Based on the findings, recommendations are made for teacher education programs and mentor teachers to better prepare pre-service teachers in handling reticent students. Finally, the study implied some limitations and provided recommendations for future research.